Practical issues in prayer during the Corona pandemic - Harbi, Abdelghaffar Saleh (Journal of Islamic Sciences, 2023)
The study aimed to clarify applied issues in prayer during the Corona pandemic, and to study them as a legal purpose study, without neglecting the opinions of the Contemporary jurists, and the fatwa houses to remove the confusion and close the door to sedition and discord. The study focused on applied issues in prayer with it related issues during the pandemic, and given the legal nature of the topic, this study relied on an inductive analytical approach, with a stop to the descriptive and the comparative approaches in some positions. The main axes of the research were the case of loss of the two purifiers, the call to prayer (azan), the distance between worshipers, and the prevention of the congregational prayers during the pandemic. The study concluded that preserving the human soul takes precedence over performing the religious duty.